Ablative liver radiotherapy for unresected intrahepatic cholangiocarcinoma: Patterns of care and survival in the United States. Issue 13 (13th April 2022) - De, Brian; Tran Cao, Hop S.; Vauthey, Jean‐Nicolas; Manzar, Gohar S.; Corrigan, Kelsey L.; Raghav, Kanwal P. S.; Lee, Sunyoung S.; Tzeng, Ching‐Wei D.; Minsky, Bruce D.; Smith, Grace L.; Holliday, Emma B.; Taniguchi, Cullen M.; et al.
Abstract : Background: Single‐institution studies have shown the oncologic benefit of ablative liver radiotherapy (A‐RT) for patients with unresectable intrahepatic cholangiocarcinoma (ICC). However, adoption of A‐RT across the United States and its associated outcomes are unknown. Methods: We queried the National Cancer Data Base for nonsurgically managed patients with ICC diagnosed between 2004 and 2018. Patients were labeled A‐RT for receipt of biologically effective doses (BED10 ) ≥ 80.5 Gy and conventional RT (Conv‐RT) for lower doses. Associations with A‐RT use and overall survival were identified using logistic and Cox regressions, respectively. Results: Of 27, 571 patients, the most common treatments were chemotherapy without liver RT (45%), no chemotherapy or liver RT (42%), and liver RT ± chemotherapy (13%). Use of liver RT remained constant over time. Of 1112 patients receiving liver RT with known doses, RT was 73% Conv‐RT (median BED10, 53 Gy; median, 20 fractions) and 27% A‐RT (median BED10, 100 Gy; median, 5 fractions). Use of A‐RT increased from 5% in 2004 to 48% in 2018 ( P trend < .001). With a median follow‐up of 52.3 months, median survival estimates for Conv‐RT and A‐RT were 12.8 and 23.7 months ( P < .001), respectively. On multivariable analysis, stage III and IV disease correlated with a higher risk of death, whereas chemotherapy and A‐RT correlated with a lower risk. Conclusions: Although A‐RT has been increasingly used, use of liver RT as a whole in the United States remained constant despite growing evidence supporting its use, suggesting continued unmet need. A‐RT is associated with longer survival versus Conv‐RT. Lay Summary: Bile duct cancer is a rare, deadly disease that often presents at advanced stages. Single‐institution retrospective studies have demonstrated that use of high‐dose radiotherapy may be associated with longer survival, but larger studies have not been conducted. We used a large, national cancer registry of patients diagnosed between 2004 and 2018 to show that liver radiotherapy use remains low in the United States, despite growing evidence that patients who receive it live longer. Furthermore, we showed that patients who received high‐dose radiotherapy lived longer than those who received lower doses. Greater awareness of the benefits of liver radiotherapy is needed to improve patient outcomes. Abstract : In this analysis of 27, 571 patients in the United States with unresected intrahepatic cholangiocarcinoma diagnosed between 2004 and 2018, use of liver radiotherapy remained constant despite growing evidence supporting that its use is associated with longer survival. Among patients who received liver radiotherapy, higher doses have been increasingly used; patients who received higher doses had longer survival than those receiving lower doses (median 23.7 vs 12.8 months, respectively).